2023
DOI: 10.1002/adfm.202305372
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Dispersed Sn Confined in FeS2 for Nitrate‐to‐Ammonia Electroreduction

Guike Zhang,
Fuzhou Wang,
Kai Chen
et al.

Abstract: Electrocatalytic NO3− reduction to NH3 (NO3RR) is an efficient strategy to simultaneously mitigate NO3− contamination and produce sustainable NH3. Herein, atomically dispersed Sn confined in FeS2 (Sn‐FeS2) is reported as an effective and robust NO3RR catalyst, achieving a maximum NH3‐Faradaic efficiency of 96.7% with a corresponding NH3 yield rate of 15.8 mg h−1 cm−2, along with an excellent catalytic stability. Atomic coordination characterizations of Sn‐FeS2 unravel that single‐atomic Sn bonds with the surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…In the spectra, the negative bands at ∼1350 cm −1 indicated NO 3 − , and the positive bands at ∼1120 and ∼1410 cm −1 were attributed to protonation (*NH x ) intermediates. 37 Increasing the current applied to the TTAB-CNT electrocatalyst (Figure 3b) steadily increased the intensity of the *NH x intermediates and also the symmetric deformation vibration of adsorbed NH 4 + (δ s NH 4 + , ∼1680 cm −1 ). 38 This increase demonstrated that TTAB-CNT could efficiently promote NO 3 − activation and protonation, leading to the successful generation of NH 3 .…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the spectra, the negative bands at ∼1350 cm −1 indicated NO 3 − , and the positive bands at ∼1120 and ∼1410 cm −1 were attributed to protonation (*NH x ) intermediates. 37 Increasing the current applied to the TTAB-CNT electrocatalyst (Figure 3b) steadily increased the intensity of the *NH x intermediates and also the symmetric deformation vibration of adsorbed NH 4 + (δ s NH 4 + , ∼1680 cm −1 ). 38 This increase demonstrated that TTAB-CNT could efficiently promote NO 3 − activation and protonation, leading to the successful generation of NH 3 .…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Operando FTIR monitored the absorbed intermediate species of the NO 3 RR using a current ranging from OCP to 20 mA (Figure a–c). In the spectra, the negative bands at ∼1350 cm –1 indicated NO 3 – , and the positive bands at ∼1120 and ∼1410 cm –1 were attributed to protonation (*NH x ) intermediates . Increasing the current applied to the TTAB-CNT electrocatalyst (Figure b) steadily increased the intensity of the *NH x intermediates and also the symmetric deformation vibration of adsorbed NH 4 + (δ s NH 4 + , ∼1680 cm –1 ) .…”
Section: Resultsmentioning
confidence: 98%
“…The electrocatalytic synthesis of ammonia from nitrate using non-noble metal-based catalysts is a more flexible and low-cost method. Non-noble transition metals, such as Cu, Fe, and Co, are catalytically active for the NITRR process, and Cu-based catalysts exhibit great activities. As an ideal support for metal nanoparticles, porous carbon materials can not only reduce the aggregation of nanoparticles but also promote electron and mass transfer. Encapsulation and confinement of Cu nanoparticles in porous carbon frames by high-temperature carbonization is a promising approach to increase the activity, selectivity, and stability of Cu-based electrocatalysts. , Metal–organic frameworks have been considered ideal templates for the fabrication of carbon-supported metal nanoparticles because the use of the coordination metal and monomer can be adjusted and is flexible, and high specific surface areas and uniform active structures can be achieved. However, carbon-supported single metallic Cu-based catalysts often suffer from significant deactivation during long-term operation due to surface passivation, metal leaching, and particle aggregation …”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the century-old Haber–Bosch process based on the reaction of high-purity hydrogen (H 2 ) and N 2 (N 2 + 3H 2 → 2NH 3 ) over an iron catalyst at high temperatures (400–600 °C) and pressures (20–40 MPa) still dominates the industrial NH 3 production and contributes more than 170 million tons of global output annually. However, dependence on natural gas for H 2 manufacture (CH 4 + 2H 2 O → 4H 2 + CO 2 ) also results in massive consumption of fossil fuels and carbon dioxide (CO 2 ) emissions (over 300 million tons per year), and a more green sustainable strategy enabling N 2 fixation is therefore highly desirable. , Electrochemical NH 3 synthesis, relying on renewable electricity for power, is recognized as a promising alternative to the energy-intensive and CO 2 -extensive Haber–Bosch process for industrial-scale production, owing to its milder operating condition, lower energy consumption, and more abundant raw material. It not only produces NH 3 from air and water under ambient temperature and pressure (2N 2 + 6H 2 O → 4NH 3 + 3O 2 ) but also uses other nitrogen-containing compounds in the environment as feedstocks, such as nitric oxide (NO) and nitrate (NO 3 – ). In particular, the second pathway, which can transform the waste nitrogen sources originating from fuel burning, vehicle exhaust, agricultural and industrial sewage, or other harmful pollutants into valuable NH 3 (NO + 5H + + 5e – → NH 3 + H 2 O or NO 3 – + 6H 2 O + 8e – → NH 3 + 9OH – ) is therefore considered as a “one stone two birds” strategy. Unfortunately, the reaction rate and Faradaic efficiency (FE) for the above processes are relatively low without a catalyst, owing to the chemical inertness and the competitive hydrogen evolution reaction in an aqueous electrolyte. The development of highly active and selective catalysts is thus of great significance for the industrialization of electrochemical NH 3 synthesis. …”
Section: Introductionmentioning
confidence: 99%